N‐homocysteinylation of α‐synuclein promotes its aggregation and neurotoxicity. Issue 3 (27th November 2022) - Zhou, Lingyan; Guo, Tao; Meng, Lanxia; Zhang, Xingyu; Tian, Ye; Dai, Lijun; Niu, Xuan; Li, Yiming; Liu, Congcong; Chen, Guiqin; Liu, Chaoyang; Ke, Wei; et al.
Abstract: The aggregation of α‐synuclein plays a pivotal role in the pathogenesis of Parkinson's disease (PD). Epidemiological evidence indicates that high level of homocysteine (Hcy) is associated with an increased risk of PD. However, the molecular mechanisms remain elusive. Here, we report that homocysteine thiolactone (HTL), a reactive thioester of Hcy, covalently modifies α‐synuclein on the K80 residue. The levels of α‐synuclein K80Hcy in the brain are increased in an age‐dependent manner in the TgA53T mice, correlating with elevated levels of Hcy and HTL in the brain during aging. The N‐homocysteinylation of α‐synuclein stimulates its aggregation and forms fibrils with enhanced seeding activity and neurotoxicity. Intrastriatal injection of homocysteinylated α‐synuclein fibrils induces more severe α‐synuclein pathology and motor deficits when compared with unmodified α‐synuclein fibrils. Increasing the levels of Hcy aggravates α‐synuclein neuropathology in a mouse model of PD. In contrast, blocking the N‐homocysteinylation of α‐synuclein ameliorates α‐synuclein pathology and degeneration of dopaminergic neurons. These findings suggest that the covalent modification of α‐synuclein by HTL promotes its aggregation. Targeting the N‐homocysteinylation of α‐synuclein could be a novel therapeutic strategy against PD. Abstract : Hyperhomocysteinemia is associated with an increased risk of PD. However, the molecular mechanisms remain elusive. HTL, a reactive thioester of Hcy, covalently modifies a‐synuclein at the K80 residue. The N‐homocysteinylation of a‐synuclein stimulates its aggregation and neurotoxicity. Our findings suggest that targeting the N‐homocysteinylation of a‐synuclein could be a novel therapeutic strategy against PD.